Critical analysis of Chapter 23 of Keynes's Notes on Mercantilism in The General Theory of Employment, Interest and Money (1936) - Aleksandar Vasilev; Rashid Maksumov (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2010)
Critical analysis of Chapter 23 of Keynes's Notes on Mercantilism in The General Theory of Employment, Interest and Money (1936).
Keywords: A1; 330; Keynes; mercantilism